THE ROLE OF TEACHERS IN INCREASING ACHIEVEMENT MOTIVATION THROUGH PROBLEM SOLVING-BASED CIVIC LEARNING FOR STUDENTS - Ria Melleni Hamidiyah; Ajar Dirgantoro (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2023)
This study aims to determine the role of teachers in increasing Achievment Motivation through Civic education learning. The research method used is qualitative with a narrative descriptive approach. The subjects in thisstudy were civic education teachers and the learning model they used. The instruments used in this study were observation, interviews, interview drafts, focus group discussions and documentation. The result of this study is that there are two roles of teachers in increasing achievement motivation, namely teachers as motivators and teachers as facilitators.